2017
DOI: 10.1002/advs.201700667
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Photon Upconversion and Precise Control of Donor–Acceptor Interaction through Interfacial Energy Transfer

Abstract: Upconverting materials have achieved great progress in recent years, however, it remains challenging for the mechanistic research on new upconversion strategy of lanthanides. Here, a novel and efficient strategy to realize photon upconversion from more lanthanides and fine control of lanthanide donor–acceptor interactions through using the interfacial energy transfer (IET) is reported. Unlike conventional energy‐transfer upconversion and recently reported energy‐migration upconversion, the IET approach is capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 58 publications
0
62
0
Order By: Relevance
“…Spatially separation of Tm 3+ and Eu 3+ in different layers by using NaNdF 4 :Yb as an intermediate layer resulted in a consistent strong Tm 3+ emission with negligible Eu 3+ emissions, implying that Tm 3+ in this configuration serves as not only emitters, but also energy accumulators to store the excitation energy (Figure 2G, H). Gd 3+ with an optimal concentration of 50 mol% acts as energy migrator in the intermediate shell for bridging of the energy gap through energy migration, being consistent with the previous report (Figure S10, Supporting Information) . To further demonstrate the rational behind our particles, we synthesized another two types of UCNPs, NaGdF 4 :Yb,Tm@NaGdF 4 :Eu@NaNdF 4 :Yb and NaGdF 4 :Eu@NaGdF 4 :Yb,Tm@NaNdF 4 :Yb as control experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Spatially separation of Tm 3+ and Eu 3+ in different layers by using NaNdF 4 :Yb as an intermediate layer resulted in a consistent strong Tm 3+ emission with negligible Eu 3+ emissions, implying that Tm 3+ in this configuration serves as not only emitters, but also energy accumulators to store the excitation energy (Figure 2G, H). Gd 3+ with an optimal concentration of 50 mol% acts as energy migrator in the intermediate shell for bridging of the energy gap through energy migration, being consistent with the previous report (Figure S10, Supporting Information) . To further demonstrate the rational behind our particles, we synthesized another two types of UCNPs, NaGdF 4 :Yb,Tm@NaGdF 4 :Eu@NaNdF 4 :Yb and NaGdF 4 :Eu@NaGdF 4 :Yb,Tm@NaNdF 4 :Yb as control experiments.…”
Section: Resultsmentioning
confidence: 99%
“…This finding enhanced the applicability in optical encoding of this parameter. Based on this theory, Zhang’ group have demonstrated that inter‐facial energy transfer is an efficient and more general strategy for exporting upconversion luminescence of lanthanides (Figure c–d) . This finding may help to manipulate and control photo upconversion at a single lanthanide ion level.…”
Section: Smart Luminescent Materials For Optical‐encodingmentioning
confidence: 95%
“…[3] The unique luminescent characteristics and energy transfer variety impart lanthanide materials great potentials in a wide range of fields, including but not limited to display and lighting, [4,5] laser, [6] information security, [7][8][9][10] sensing and detection, [11][12][13][14][15] biological imaging and therapy, [16][17][18] photocatalysis, and optoelectronic device. [28][29][30][31][32][33][34][35][36] All these methods based on synthetic chemistry in fact only change the basic physical processes, that is, excitation, energy transfer, nonradiative transition, and emission, involved in lanthanide luminescence mechanism. For example, multicolor emissions are expected for anti-counterfeiting, full-color display, and lighting, [23,24] red and near-infrared excitation and emissions are more suitable for biomedical treatment, [25,26] while ultraviolet, violet, and blue light are favored for photocatalysis and photovoltaic purposes.…”
Section: Introductionmentioning
confidence: 99%